Meningkatkan Hasil Belajar Matematika Konsep Peluang melalui Pendekatan Kontekstual pada Siswa Kelas XI GP SMK Negeri 2 Karang Baru Kabupaten Aceh Tamiang Semester - Sri Wahyuni (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
This Classroom Action Research (CAR) was carried out considering the importance of efforts to improve the quality of learning outcomes through various ways or optimal learning strategies, where the teacher plays a very important role in preparing students to take part in learning. The Contextual Method was chosen to improve learning outcomes of the Concept of Opportunity in class XI GP students of SMK Negeri 2 Karang Baru, Aceh Tamiang Regency, Even Semester of the 2021/2022 Academic Year. This is deemed necessary because interest and motivation as well as student learning outcomes in the class are still low. The subjects of this study amounted to 22 people. The research data was obtained by using a performance test in the form of a program using the concept of opportunity and an observation sheet. From the results of this study, it was revealed that students' ability to calculate permutations and combinations could be improved. The average value of student learning outcomes from cycle I and cycle II continued to increase (from 80.22 to 87.6) with the category of students completing cycle I (73%) and cycle II (100%).